APPLICATION OF SNAKE GAME LEARNING MEDIA LADDER ON RESPIRATORY SYSTEM MATERIAL IN CLASS VIII SMP NEGERI 10 BANDA ACEH - Zahara, Nurlia; Chaera, Miftahul (Prosiding Seminar Nasional Biologi, Teknologi dan Kependidikan, 2024)
In learning, students feel less enthusiastic and less interesting in the learning process because students are only focused on the teacher and the package book so that students only listen so that there is no interaction by students. Efforts in overcoming these problems are one of them with the application of snakes and ladders game learning media. The purpose of this study was to determine the learning outcomes of students in class VIII SMP Negeri 10 Banda Aceh. This study used a pre-experimental method using a one group pretest-posttest desaign type of design. The population in this study were all students of class VIII A SMP Negeri 10 Banda Aceh, while the sample in this study were class VIII A students totalling 26 students. The technique in collecting data in this study was using pre-test and post-test test questions. Analysis of learning outcomes using the N-Gain formula and t-test. The results showed that the first day student learning activity was 80% including the Very Active category. The second meeting there was an increase in student learning activities, namely an average percentage value of 91.37% including the Very Active category. Analysis of student learning outcomes seen from the data obtained t-count of 45.69 and t-table obtained by 2.059. The results of these calculations can be concluded that tcount> ttable (45.69> 2.059) so that Ha is accepted while H0 is rejected.Key words: Snakes and Ladders Media, Respiratory System, Learning Outcomes